Is the environmental policies procedures a barrier to development of inland navigation and port management? A case of study in Brazil - Kaiser, Ilza Machado [UNESP]; Bezerra, Barbara Stolte [UNESP]; Castro, Leslie Ivana Serino [UNESP] (Elsevier, 2013)
The main objective of this article is to discuss the Brazilian environmental legislation and policies towards the development of navigation and port management. The research illustrated some difficulties faced by the country and make suggestions to overcome it. The construction of the environmental legal framework began in the early 1960s and resulted in a very complex system, as a consequence of policies adopted by the country. Nowadays Brazilian environmental policies are developed in democratic and participative way, although with elevated degree of bureaucracy and lack of integration among the several governmental agencies, which makes the approval of environmental certifications demand several years for new port projects or improvements, which delays the economic development of the country. Efforts have been made to simplify the licensing process. As result of this research two flowchart for environmental licenses of ports installation are shown: The first shows the process until 2009 and the second shows the process nowadays. This become an important issue due the fact that inland navigation is one of the less pollutant modes of transportation, and although, the process of environmental certification was simplified, if compare with 2009, it is still complex and time-consuming, delaying the development of the infrastructure. © 2012 Elsevier Ltd.
Keywords: Environment legislation; Environmental permitting; Inland navigation; Port; Port installation; Economic development; Environmental certification; Environmental legislations; Environmental policy; Governmental agency; Legal frameworks; Licensing process; Port management; Laws and legislation; Navigation; Environmental protection; bureaucracy; certification; economic development; environmental legislation; environmental policy; navigation; port development; port installation; Brazil